Plasmon Hybridization in Stacked Double Crescents Arrays Fabricated by Colloidal Lithography - Vogel, Nicolas; et al. (Nano Letters, 2011)
We apply colloidal lithography to construct stacked nanocrescent dimer structures with an exact vertical alignment and a separation distance of approximately 10 nm. Highly ordered, large arrays of these nanostructures are accessible using nonclose-packed colloidal monolayers as masks. Spatially separated nanocrescent dimers are obtained by application of spatially distributed colloids The polarization dependent optical properties of the nanostructures are investigated in detail and compared to single crescents. The close proximity of the nanocrescents leads to,a coupling process that gives rise to new optical resonances which can be described as linear superpositions of the individual crescents plasmonic modes. We apply a plasmon hybridization model to explain the spectral differences of all polarization dependent resonances and use geometric arguments to explain the respective shifts of the resonances. Theoretical calculations are performed. to support the hybridization model and extend it to higher order resonances not resolved experimentally.
Keywords: Nanosphere lithography; nanostructures; split ring resonators; metamaterials; plasmons; plasmon hybridization